2021
DOI: 10.1021/acsomega.1c03795
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible CuInS2 Nanoparticles as Potential Antimicrobial, Antioxidant, and Cytotoxic Agents

Abstract: A simple hydrothermal route is employed to synthesize pure copper indium disulfide (CIS) and CIS nanoparticles (NPs) mediated by various natural plant extracts. The plant extracts used to mediate are Azadirachta indica (neem), Ocimum sanctum (basil), Cocos nucifera (coconut), Aloe vera (aloe), and Curcuma longa (turmeric). The tetragonal unit cell structure of as-synthesized NPs is confirmed by X-ray diffraction. The analysis by energy-dispersive X-rays shows that all the samples are nearstoichiometric. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…Different values of Z can be acquired by solving eqn (13). The positive and real value of 'Z' is utilised to obtain the extinction coefficient from eqn (14).…”
Section: Dielectric Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different values of Z can be acquired by solving eqn (13). The positive and real value of 'Z' is utilised to obtain the extinction coefficient from eqn (14).…”
Section: Dielectric Constantsmentioning
confidence: 99%
“…In the ever-expanding family of three-dimensional materials, for photonic applications, notably in the field of flexible optoelectronics, those having semiconducting properties of transition metal dichalcogenides (TMDCs) are of particular interest in recent advances. The TMDCs are of great attention to researchers due to the variety of their structural and electrical characteristics, such as thermoelectric effect, 1,2 thermal study, [3][4][5][6] superconductivity, 7,8 optical study, 9,10 photovoltaic devices, 11,12 biological applications, [13][14][15][16] etc. Among the TMDCs, chalcopyritetype semiconducting materials are being sought for their equally significant and environmentally benign nature, as well as prospective applications in a variety of optical instruments in the visible and near-infrared regions.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesized nanoparticles are tested for their antimicrobial efficacy using the agar-well diffusion method. , Further, 1 mL of inoculum of each indicator organism is combined with warm nutrient agar and then spread over the Petri plates to acquire a uniformly thick lawn of bacterial growth. Narrow wells of 7 mm in diameter are bored into nutrient agar plates, and 50 μL of each nanoparticle suspension (25 μg/mL in 10% DMSO) is individually added into each well.…”
Section: Resultsmentioning
confidence: 99%
“…The remarkable antioxidant capabilities of the nanoparticles are assessed by employing DPPH radical scavenging testing. 49 2,2-Diphenyl-1-picrylhydrazyl (DPPH) is a steady free radical at ambient temperature that receives an electron from synthesized nanoparticles that transforms it into a stable diamagnetic molecule that discolors the DPPH solution. A DPPH solution of 1 mM in methanol is made.…”
Section: Antioxidant Studymentioning
confidence: 99%
“…In recent years, with the continuous in-depth research of nanomaterials compared with traditional antitumor treatments, nanomaterials have been used in more and more clinical anticancer applications, showing great development potential [ 111 ]. For example, in our previous research, we found that some nanoparticles, such as superparamagnetic iron oxide nanoparticles (SPIONs), high-Z gold nanoparticles following intratumoral injection can provide a high local concentration of the agent, reduction of the particle clearance (i.e., renal or hepatic clearance) that increases the bioavailability of nanoparticles and has the effect of radiosensitizer in cancer radiotherapy, which can be used for long-term local anti-tumor therapy [ 112 , 113 ].…”
Section: Clinical Application Of Copper-based Nanoparticles In Oncologymentioning
confidence: 99%